Cardioprotection and Thyroid Hormones in the Clinical Setting of Heart Failure - Francesca Mastorci; Laura Sabatino; Cristina Vassalle; Alessandro Pingitore (Frontiers in Endocrinology, 2020)
Ischemic heart disease is the main cause of morbidity and mortality worldwide and is becoming more widespread with population aging. Cardioprotection is a dynamic process characterized by mechanisms related to myocardial damage and activation of protective factors. Targeting these processes could be attractive as a new therapeutic strategy in the evolution of post-ischemic heart failure (HF). In this context, the role of thyroid hormone (TH)-mediated cardioprotection is supported by a number of findings regarding the modulation of neuroendocrine systems, inflammatory and oxidative stress status, pro-survival intracellular pathways, and epigenetic factors, its effects on cardiac angiogenesis, structure, and function and on the preservation of mitochondrial function and morphology, and its beneficial effects on cell growth and redifferentiation. Moreover, the numerous effects of TH on the heart involve genomic mechanisms, which include cardiac differentiation during the perinatal period and non-genomic action, directed toward the maintenance of cardiovascular homeostasis. This evidence suggests that there is an opportunity to treat HF patients with TH. This review is mainly focused on the clinical evidence of the role of the thyroid system in the complex setting of HF.